Filipino women inventors commercialization of their award-winning inventions, a case study - Claridad, Ma. Lourdes Bernadette V.; Cruz, Edison D. (Quezon City University of the Philippines Diliman, 2007)
Women inventors and their inventions have contributed to the national development and progress. This paper provides a case study of award-winning Filipino women inventors and their corresponding invention/s; find out which if these existing inventions made it to full commercialization. The paper also presents a comparison of Filipino Women Inventors with Women Inventors from other select countries. The paper also provides useful information and insights that will be most beneficial to the Inventors, TAPI-DOST, and the Academe. The paper focused on the members of Association of Filipino Women WIPO Awardees (AFWWA), composed of women who have been awarded and recognized by the World Intellectual Property Organization (WIPO) for their outstanding invention/s. Successfully commercialized inventions were assessed according to the factors that contributed to its success, and the problems they have encountered in the course of commercialization. Out of the 26 members of the AFWWA, only 3 were feasible for interview. The rest cannot be contacted by phone, email or even snail mail at the time of this paper's writing. The three women inventors are : Mrs. Erlinda Sanqui, who won Most Outstanding Women Inventor in 1990; Mrs. Carlita Rex Doran, who won Most Outstanding Women Inventor in 1989 and Most Outstanding Inventor in 1991; and Mrs. Leonora Dominguez, who (together with other DOST employees) won Most Outstanding Invention in 1994. A short interview questionnaire was used to elicit information on the background of the inventor and her inventions, her experiences towards the commercialization of her inventions, factors that contributed to her success and the problems she encountered in the path to commercialization. The Inventors. Elinda Sanqui has been a teacher for 27 years when she decided to venture into the catering business. She experimented with different types of ingredients, especially local food raw materials. Among her inventions were the Fruit Cake Filipina, which made use of local fruits and wines as substitutes for the westernized ingredients of the traditional fruit cake. She formulated innovative techniques in food preparation which led to the development of various processed foods. These include the tamarind nectar concentrate, tamarind jam, sweet sour sauce from tamarind, honeyed tamarind candy, salt-free herbal blend seasoning, home-made labong (bamboo shoot) pickles, herb vinegar, herb oil, herbal tea blends (lagundi, sambong, banaba, ampalaya, guyabano, mango, guava), different dessert food items, and the more popular pito-pito herbal tea. Sanqui's products are sold under the Rita Ritz Bakehouse and Food Products Brand. Most of her products are available in Mercury Drugstores, SM Supermarkets and other selected retail stores. Another prolific women inventor is Carlita Rex Doran. She is chemist by profession and had vast professional experience before she set up her own manufacturing company of chemicals for industrial and household use. Doran formulated an instant fuel formulation, Siroca, which had various applications-cooking for households, restaurants and other establishments. It also used for outdoors activities, like camping. Soon, she was exporting Siroca to Japan, Hong Kong, Singapore and Kuwait. Doran eventually ventured into herbal cosmetics and food supplements, with the philosophy, "Go Natural...Go Herbal". She was the one who pioneered the use of gugo in commercialized shampoos. She also used tawas for skin & body care products. She launched her products under the Forest Magic brand. From an initial P1,000.00 capital, Doran's company, CRD is now a multi-million venture. The company toll-manufacturers for other companies, which include Bioessence Facial & Slimming Center, Oro Laboratories and other dermaclinics and skin care centers. CRD also has international clients from UAE, Korea, Thailand and Europe. A group of employees from Fuels & Energy Division and Chemicals & Minerals Division of the DOST were able to formulate "A Process for the Production of Slow Release Type Potassium Silicate Fertilizer from Rice Husks and Dolomic Limestone and the Product Thereof". The group, led by Engr. Leonora Dominguez, formulated an industrial process for preparing and formulating a slow release type fertilizer from locally available indigenous raw materials such as rice husk, dolomitic limestone, potassium carbonate, saw dust and molasses using an internal heat-type fluidized bed reactor. The product is insoluble in water but highly soluble in acidic condition of the soil. Unfortunately, the project never left the pilot scale phase and never reached the commercialization stage. Since the project was under a government agency, it lacked the funds to move it to the next stages. According to Dominguez, insufficiency of funds made it impossible for them to do a feasibility study on the product and process. Another problem was the lack of equipment competent researchers. The project is temporarily shelved. Analysis. The women inventors have encountered problems in their paths to commercialization of the inventions. The biggest obstacle is the lack of financial support from the government. Even with the Inventor and Inventions Incentives Act of the Philippines (RA 7459), "an act approving incentives to Filipino inventors and expanding the functions of the Technology Application and Promotion Institute, appropriating funds therefore, and for other purposes.", inventors are still wanting of financial help. The act provides yearly P10 million appropriation to the Invention Guarantee Fund to pay for the finance and guarantee of loan assistance, cash rewards and other incentives to inventors provided under this Act.
Another problem is the sustainability of the DOST-TAPI's projects for the inventors. TAPI-DOST is the lead government institute mandated to help the inventors. But due to Philippine bureaucracy, the head of the agency would be changed every a few years. Some heads would initiate good projects for the inventors, others not even sympathetic to the needs of the inventors. There is no continuity of very good projects that have been implemented. Due to lack of funds, the inventions have very simple packaging. This is one area where the inventors also need assistance. The DOST Industrial Technology Development Institute's Packaging R&D Center can assist in the development of the packaging of some products. However, the problem lies on which supplier the inventors will approach to produce the packaging. Most packaging suppliers have a very high minimum order quantity (at least 20,000 pieces), which is very prohibitive for someone who is just starting. Packaging is very important in marketing a product. No matter how good the product is, it is still the packaging that the customers first notice and attracts them to buy the product. Another problem faced by the women inventors is the lack of recognition for them as women inventors. Not many people know that there are associations for women inventors or even scientists. For sure there are a lot of other women, given the fact, would want to join these associations. Being members of the association have benefits. WIAPI is one of the accredited inventor associations by the TAPI-DOST. One must be certified or her invention must be certified by WIAPI so that the inventor may avail of the benefits stipulated in the Inventor and Inventions Incentives Act of the Philippines. In comparison, with women inventors from Malaysia and Japan, Filipino women inventors are lacking in government support. Women inventors who have become successful entrepreneurs or technopreneurs have the full support of their families. Their families help them in running the business. One reason that an inventor would rather keep the invention inside her family is to protect her formulations and trade secrets from unscrupulous people, who would take advantage of her knowledge and know-how and leave her in the dark after they have gotten everything they can learn from her. Conclusion & Recommendations. The inventors must have a patron who will champion their cause. He/She should be somebody influential in business and in the foreign markets. The patron of the inventions must be able to promote the creative/inventive spirit throughout the nation and be able to campaign for Filipino inventions to other countries. The tap inventors must have the support of the government-academe-industry. The TAPI-DOST must be the one to initiate and lobby for the changes in RA 7459 to make it more applicable to today's settings. TAPI-DOST must also bring the National Inventors Week to other places in the country to promote the inventive spirit in the provinces. The academe should open its laboratories and libraries to the inventors so they could further test their prototypes and research more on their inventions. The industry must support the inventors as they had supported the Go Negosyo campaign. Without enterprising spirits, inventors would not be able to go far in marketing and making available these products. The Women Inventors Association of the Philippines (WIAPI) must embark on an aggressive marketing campaign to promote the women inventors. Intensive recruitment efforts should also be done to bring in new blood into the organization. Potential members must know the advantages of being part of the WIAPI. By being members, they will be able to avail of the benefits of Republic Act 7459.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Women inventors -- Philippines; Inventions